Removal of lead by sulfate-reducing bacteria in anaerobic continuous stirred tank reactors - Yên, Nguyễn Thị; Hoa, Kiều Thị Quỳnh (Vietnam Journal of Biotechnology, 2016)
Lead contaminated wastewater negatively impacts to living organisms as well as humans. In recent years, a highly promising biological process using the anaerobic production of sulfide ions by sulfate-reducing bacteria has presented itself as an alternative option for the removal of lead. This process is based on microbial utilization of electron donors, such as organic compounds (carbon sources), and sulfate as the terminal electron acceptor for sulfide production. The biogenic hydrogen sulfide reacts with dissolved heavy metals to form insoluble metal sulfide precipitates Removal of lead by an enriched consortium of sulfate-reducing bacteria (DM10) was evaluated sulfate reduction, sulfide production and lead precipitation. Four parallel anaerobic continuous stirred tank reactors (CSTR, V = 2L) (referred as R1 - R4) were fed with synthetic wastewater containing Pb2+ in the concentrations of 0, 100, 150 and 200 mg L-1 of lead and operated with a hydraulic retention time of 5 days for 40 days. The loading rates of each metal in R1- R4 were 0, 20, 30 and 40 mg L-1 d-1, respectively. The results showed that there was no inhibition of SRB growth and that lead removal efficiencies of 99-100% for Pb2+ were achieved in R2 (100 mg L-1) and R3 (150 mg L-1) throughout the experiment. For the highest lead concentration of  200 mg L-1, a decrease in efficiency of removal (from 100 to 96%) was observed at the end of the experiment. The obtained result of this study might help for a better control operation and performance improvements of reactors.